2013
DOI: 10.1002/oti.1346
|View full text |Cite
|
Sign up to set email alerts
|

International Research Partnerships in Occupational Therapy: A Canadian–Zambian Case Study

Abstract: The country of Zambia's Sixth National Development Plan includes many objectives related to participation and health that align with values underlying occupational therapy. Given this link, occupational therapy research has the potential to advance the Sixth National Development Plan and thereby enhance the participation and health of Zambians. However, there is neither a school of occupational therapy nor many occupational therapists working in Zambia. Using an example of a global research partnership between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…The findings of this study is in agreement with previous studies that indicated shortage of rehabilitation healthcare workforce [20, 23, 29, 34–36] and limited OT and PT training programs [32, 33, 35–38] in some SSA countries. For the past 65 years, WFOT and WCPT have been strong advocates for their respective professions [19, 36, 39, 40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study is in agreement with previous studies that indicated shortage of rehabilitation healthcare workforce [20, 23, 29, 34–36] and limited OT and PT training programs [32, 33, 35–38] in some SSA countries. For the past 65 years, WFOT and WCPT have been strong advocates for their respective professions [19, 36, 39, 40].…”
Section: Discussionsupporting
confidence: 92%
“…The extent to which African perspectives are considered in the framing of the entry-level OT competencies should be examined [53]. Seventh, efforts should be made to identify and replicate effective models of international cooperation and partnership on the training and education of PT and OT [38, 40]. Eight, in order to obtain an accurate number of native-born and expatriate practicing PT and OT, an effort should be made to obtain information directly from professional licensing and government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of guidelines exist for north–south health research collaborations [4, 5, 46, 55, 56]. For the most part, these rules of research collaborations were broadly adhered to in the collaborations explored in this study, including for example the principles of honesty, accountability, professional courtesy, fairness and good stewardship, as outlined in the Montreal Statement on Research Integrity (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Interdisciplinary research is an expectation in funded research, and the group involved is highly valued. Global partnerships where collaboration unites complementary skills and knowledge are needed to solve global health problems 16 .…”
Section: Final Considerationsmentioning
confidence: 99%